2014
DOI: 10.1021/jp5113125
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Asymmetry in the Multiphoton Ionization of Methyloxirane Using Femtosecond Electron–Ion Coincidence Imaging

Abstract: Multiphoton photoelectron circular dichroism (MP-PECD) has been observed as an asymmetry in the angular distribution of photoelectrons emitted in the ionization of pure enantiomers of the small chiral molecule methyloxirane using a femtosecond laser operated at 420 nm. Energetically, this requires the uptake of four photons. By switching the laser between left- and right-circular polarization, and observing the differences in the full three-dimensional electron momentum distribution recorded in an electron-ion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 28 publications
1
23
0
Order By: Relevance
“…Some further measurements were made with a 3 kHz, 150 fs pulse duration laser coupled with a dual imaging electron‐ion coincidence spectrometer, again as previously described [41–43] …”
Section: Methodsmentioning
confidence: 99%
“…Some further measurements were made with a 3 kHz, 150 fs pulse duration laser coupled with a dual imaging electron‐ion coincidence spectrometer, again as previously described [41–43] …”
Section: Methodsmentioning
confidence: 99%
“…One of them is in the single photon ionization regime showing a rich dependency on the fragmentation channel. The other two , are in the (resonant) multiphoton regime revealing no dependency on the fragmentation channel. Here we expand these studies to the strong field regime.…”
Section: Introductionmentioning
confidence: 98%
“…Lux et al [9] measured a ∼15% PECD in (2+1) resonance-enhanced multiphoton ionization (REMPI) of fenchone and camphor where two photon absorption brings the molecule into an electronic excited state while the third photon ionizes the system. Since this pioneering experiment, REMPI-PECD has been measured in other compounds, in (2+1) [10][11][12] and (3+1) [13] configurations. Recently, Lux et al observed PECD in the first above threshold ionization (ATI) peak in a (2+2) scheme [14].…”
Section: Introductionmentioning
confidence: 99%